2019
DOI: 10.3389/fmicb.2019.01539
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Single Strains of Listeria monocytogenes and Salmonella Typhimurium Planktonic Cells Biofilms With Plasma Activated Liquids

Abstract: Recent research has proven the ability of cold atmospheric plasma (CAP) for assuring food safety. A more flexible and transportable alternative is the use of plasma activated liquids (PAL), which are also known to have antimicrobial properties. However, within the context of food safety, little is known on its potential regarding decontamination. This research therefore focusses on identifying the impact of (i) the microbial species and its cell type (planktonic cells or biofilms), (ii) the CAP settings (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 47 publications
4
59
0
Order By: Relevance
“…Around 5 log reduction was obtained after 30-min exposure with PAW immediately after generation. Smet et al (2019) studied the inactivation efficacy of PAW against L. monocytogenes and Salmonella Typhimurium in planktonic and biofilm state using a cold atmospheric plasma, along with which the impact of different gas composition, PAW generation time and exposure time were investigated. The results showed that L. monocytogenes were more resistant to PAW than S. Typhimurium when treated by the same conditions, and bacteria in planktonic state was easier to inactivate than biofilm state for both species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 5 log reduction was obtained after 30-min exposure with PAW immediately after generation. Smet et al (2019) studied the inactivation efficacy of PAW against L. monocytogenes and Salmonella Typhimurium in planktonic and biofilm state using a cold atmospheric plasma, along with which the impact of different gas composition, PAW generation time and exposure time were investigated. The results showed that L. monocytogenes were more resistant to PAW than S. Typhimurium when treated by the same conditions, and bacteria in planktonic state was easier to inactivate than biofilm state for both species.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma activated water (PAW) is generated from plasma treatment of water. Recently, PAW has attracted considerable attention as it has been reported to be effective against a wide range of micro-organisms, including bacteria (Kamgang-Youbi et al 2009;Ercan et al 2013;Smet et al 2019), biofilms (Kamgang-Youbi et al 2008;Chen et al 2017;Govaert et al 2019), spores (Sun et al 2012) and yeasts (Ryu et al 2013;Guo et al 2017). There are several advantages of using PAW for microbial inactivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different approaches to PAW generation: one is to induce the plasma directly into the water and the second one involves discharges over water and hydrated surfaces [ 25,32–35 ] or gas discharge in bubbles. [ 36 ] The main disadvantage limiting the use of PAW for decontamination is the long treatment time: It takes 5–30 min on average to achieve a 4–6 log reduction in viability of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 ] The main disadvantage limiting the use of PAW for decontamination is the long treatment time: It takes 5–30 min on average to achieve a 4–6 log reduction in viability of bacteria. [ 25,31,32 ] In all conducted experiments, activated water was added to the bacterial suspension or contaminated objects (plates with adhesive bacteria) were immersed in it. Thus, it is necessary to further drain the objects during the practical application of PAW in food industry, for example, which requires additional labor and time.…”
Section: Introductionmentioning
confidence: 99%